Abordagem holística na formação de enfermeiras - Leite, Mila Moraes (2019)
Holism is a philosophical concept associated with an extendedunderstanding of phenomena, without reductionism or fragmentation. Holistic health is based on a combination of knowledge and health practices that approach the human in its physical, mental and spiritual dimensions, in an ecological-social and cosmic interaction, leading to a systemic and transdisciplinary vision of the health and disease. The purposes of this study were to identify the potentialities and weaknesses of the holistic training in a nursing undergraduate course and to highlight the suggestions of the students and professors for the holistic training. This research is a descriptive analysis with a qualitative approach that used the Discourse of the Collective Subject and the content analysis. The participants of the research were 10 students from de last semester and 5 professors from the nursing degree course. The data collection was performed through an oral interview, recorded in audio, guided by a script with guiding questions and a sociodemographic form application. Thequotes were categorized into three themes and their respective subtopics: holistic training potentialities (human comprehension in all its dimensions, global vision of a phenomenon, integrative therapies, satisfactory approach, experiences in the Basic Health Unit (BHU), first year experience, forth year experience and appropriate conditions for a holistic approach), difficulties for the holistic training (holism as a way of seeing the other, insufficient approach, limited approach to the first year, prevalence of the biological and social approach, influence of the personal values of the professor, difficulties to execute the holistic care, isolated experience,unfilled gaps, theme devaluation, the loss of emphasis of the biological approach, limited time), suggestions for the holistic training (to knowstudents realities, to prioritize the nursing care, to get deep into the tutorials topics, to change the vision of some professors, to balance the contents, to start the approach in the first year, holistic training for the professors, integration theory and practices, human understanding in all its dimensions, quality of life in the teaching work). Emphasis was given to the experiences lived in the first and second years and to the supervised curricular internship, which, together with the conceptual frameworks and the pedagogical model of the course, potentialize the holistic formation. However, there are still challenges to be overcomed for a holistic, continuous, balanced and integrated approach, without fragmentation, with the care customization based on nursing theories, professors that combinesensitivity with scientific practice, interprofessional work and permanent holistic education for professors and the health professionals